Ritual plants of Muslim graveyards in northern Israel - Dafni Amots; Lev Efraim; Beckmann Sabine; Eichberger Christian (BMC, 2006)
Abstract This article surveys the botanical composition of 40 Muslim graveyards in northern Israel, accompanied by an ethnobotanical study of the folkloristic traditions of the use of these plants in cemeteries. Three groups of plants were found to be repeated systematically and were also recognized for their ritual importance: aromatics herbs (especially Salvia fruticosa and Rosmarinus officinalis), white flowered plants (mainly Narcissus tazetta, Urginea maritima, Iris spp. and Pancratium spp.) and Cupressus sempervirens as the leading cemetery tree. As endemic use we can indicate the essential role of S. fruticosa as the main plant used in all human rites of passage symbolizing the human life cycle. The rosemary is of European origin while the use of basil is of Indian influence. The use of white flowers as cemeteries plants reflects an old European influence and almost the same species are used or their congeners. Most of the trees and shrubs that are planted in Muslim cemeteries in Israel have the same use in ancient as well in modern European cultures. In conclusion, our findings on the occurrence of plants in graveyards reflect the geographic situation of Israel as a crossroads in the cultural arena between Asia and Europe. Most of the traditions are common to the whole Middle East showing high relatedness to the classical world as well as to the present-day Europe.